INVESTOR’S PUZZLE: DECODING OWNERSHIP AND ITS IMPACT ON FIRM VALUE - Das, Nidia Anggreni; Lukviarman, Niki; Rahim, Rida; Elfarisi, Muhammad Fany (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study aims to analyze the effect of managerial Ownership, Institutional Ownership, Public Ownership firm Value. The results of the analysis show that managerial Ownership does not have a significant effect on firm Value, indicating that variations in managerial Ownership do not have a significant impact on increasing or decreasing firm Value. This is different from the findings of several previous studies that indicate a significant effect of managerial Ownership on firm Value. In contrast, institutional Ownership shows a positive and significant effect on firm Value, supporting the view that institutional Ownership plays an important role in improving corporate governance and market confidence, which ultimately increases firm Value. Meanwhile, public Ownership does not show a significant effect on firm Value, indicating that public Ownership may not have a significant impact on firm Value. From the results of this study, it can be concluded that institutional ownership is the main factors that contribute to increasing company value. In contrast, managerial Ownership and public Ownership do not show a significant influence on company value.